Correlation of learning engagement and social support affecting the academic stress of Thai high school students - Suwajo, Tanacha; Mungkornpanich, Panit; Patanapipat, Phidpibul; Luksiri, Pitpiboon; Boontanaakrapat, Ploypraplus; Nititham, Tanatham; Wainipitapong, Sorawit (International Journal of Public Health Science (IJPHS), 2024)
High school students face an elevated risk of psychological problems, with multiple determinants contributing to this vulnerability. This cross-sectional study aimed to investigate the relationship between academic stress, social support, and learning engagement among Thai high school students. A total of 109 high school students were recruited from one school located in Bangkok, Thailand. The academic stress, social support questionnaires, and learning engagement questionnaires were completed and analyzed for the correlation using Pearson’s and Spearman’s analysis. Multiple linear regression was done to determine variables influencing on academic stress. Medium level of academic stress was found (mean±SD=3.21±0.73). Academic stress was significantly correlated with social support (r=0.252, p<0.01) in a positive direction; however, the negative correlation with learning engagement did not reach statistical significance (rho=-0.108, p>0.05). Positive influence on academic stress was also found in social support (B=0.119, p<0.007), but not the learning engagement (B=-0.089, p=0.393). Thai high school students had medium level of academic stress, which correlated with and be positively influenced by social support. Our findings emphasize the importance of appropriate social support system to reduce stress and promote well-being among Thai high school students.